Kesalahan Penulisan Kata Bahasa Indonesia Pada Kain Rentang dan Papan Iklan di Tempat Umum - Muji Endah Palupi (Wanastra: Jurnal Bahasa dan Sastra, 2018)
Error writing is the crucial thing that found in the public places, especially on the banner and billboard. Sometimes, it has been written wrongly. It is known that Indonesian has a rich peculiar language that must be explored. People around it view the ad or advertisement; they will assess the ad internally and externally. It will be seen the professionalism of the ad maker. Badan Bahasa (Language Board)  of  Kemdikbud RI, has launched the print book of PUEBI on its website freely, it depends on the ad maker to revise the Indonesian using on the ad correctly and esthetically. The objective this research is to investigate the error writing of ad and its professionalism abuse on the banner and billboard at the public places. This research is using a descriptive method; the writer is to investigate and to analyze the error writing in Indonesian of ad on the banner and billboard. The output of this research is expected to be a reference to the next researcher that wants to explore error-writing research of ad or another peculiar object. Keywords: error writing, ad, Indonesian, banner and billboard